Analisis Kontribusi Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah - Barus, Rismania Br; Alistraja Dison Silalahi (ARBITRASE: Journal of Economics and Accounting, 2022)
The purpose of this study was to find out whether there has been a development in the contribution of local taxes and regional levies to district/city governments in North Sumatra Province for the 2018 to 2020 fiscal years. The type of research used is quantitative and was carried out in district/city governments in North Sumatra province. The data collection technique used was purposive sampling. The data analysis technique used is contribution analysis to determine the contribution of local taxes and regional levies. In addition to data collection in this case, the researcher obtained research data from the Districts in Figures where the data is available at the Central Bureau of Statistics. The results of the analysis show that regional tax revenues and regional levies in each Regency/City experience an increase in income every year. In the top 5 highest local tax revenues and regional levies in all North Sumatra Regencies/Cities in 2018-2021, there is a decrease in the percentage of regional tax contributions and regional levies to regional original revenues in each Regency/City. This is considered reasonable because the revenue in each regional tax and regional retribution has increased every year, followed by an increase in original regional income in all Regencies/Cities, so that the percentage of contributions seems to be decreasing every year.